LITERATURE ANALYSIS: THE ROLE OF ECONOMIC FACTORS IN INCREASING THEFT CRIMES IN INDONESIA - Gunawan Widjaja; Adrian Bima Putra (Review of International Economy and Finance, 2025)
This study discusses the role of economic factors in increasing theft crimes in Indonesia through a systematic literature analysis. This study reviews various sources that discuss the relationship between poverty, unemployment, and income inequality with the increase in theft rates. The findings indicate that the economic pressures faced by some communities encourage criminal acts, particularly theft, as an instant solution to meet their daily needs. In addition to macroeconomic factors, social aspects such as urbanisation and low education levels also contribute to the risk of this crime. This analysis also highlights the importance of a multidimensional approach in addressing theft, which should not only rely on law enforcement but also economic policy interventions such as job creation and income redistribution. The complex interaction between economic and social variables requires comprehensive strategies that can reduce crime rates while improving community welfare. The results of this study provide an empirical and theoretical basis for policymakers to develop effective and sustainable prevention programmes.